The reduction of dispersed indigo by cathodically formed 1,2,4-trihydroxynaphthalene - Sunsanee Komboonchoo (2018)
The indirect cathodic reduction of the vat dye indigo (C.I. Vat Blue 1) by cathodically reduced Lawsone (2-hydroxy-1,4-naphthoquinone; C.I. Natural Orange 6) was studied in aq. solution at different pH values. Cyclic voltammetry and spectroelectrochemistry were used to investigate the electrochemical behavior of 2-hydroxy-1,4-naphthoquinone at a hanging mercury drop electrode. The cathodic peak potential (Ep)dmeasured at 0.1 mM lawsone solution at a scan rate of 50 mV s-1changed from -425 mV at pH 7, to -730 mV at pH 11.5 and -750 mV at pH 13 (vs. Ag/AgCl, 3 M KCl). Particularly at pH values of 8-9 and 11.5-13 voltammograms indicated successful, indirect cathodic reduction of the dye in which the cathodically reduced 2-hydroxy-1,4-naphthoquinone acted as soluble mediator. The linear relationship obtained for (Ip)dvs. v1/2is indicative of a diffusion-controlled electrode reaction mechanism. In the presence of dispersed indigo, the overall cathode reaction is similar to the Ecatprocess with continuous regeneration of the electroactive species. Spectrochemical experiments were used to prove the indirect cathodic reaction of dispersed vat dyes by 2-hydroxy-1,4-naphthoquinone. © 2009 Elsevier Ltd. All rights reserved.